An Adamic incarnational Christological framework as a theological approach for African contextual ministry - Magezi, Vhumani (Missionalia, 2016)
Many African Christian thinkers and writers are responding to the foreignness of Christ in African Christianity by treating Christ under the traditional African ancestral category. However, it is our contention that the designation of the ancestral category to Christ has a tendency of diminishing the actuality of Christ as God incarnate and encouraging syncretism in African Christianity. Given this, this paper proposes and formulates an Adamic incarnational Christological model as an alternative response to the foreignness of Christ in African Christianity. In employing the anhypostastic and enhypostastic principles, we demonstrate that Jesus Christ is not a foreigner to African Christians, since the human nature he assumed in the incarnation is a general human nature which embraces all humankind. In establishing the Adam-Christ relationship in Romans 5:12-21 and 1 Corinthians 15:21-22, we advance Adam as a biblical-theological category in enhancing the relevance of Christ to Africans. It is from this perspective that our Adamic incarnational Christological model proposes that in the incarnation, God in Christ fully identified with all mankind as the New Adam, acting from the ontological depth of his divine-human existence to save African Christians from sin and all its consequences, including death and opposing spiritual forces. Thus, our own model underscores the relevance of Christ to African Christians by emphasizing Christs complete solidarity with all humanity as the New Adam.